Building Leadership Capacity for the Effective Implementation of a Professional Development Tool in K-12 School in a Region in Arctic Canada - Osbourne, Sonia (Scholarship@Western, 2020)
This Organizational Improvement Plan (OIP) aims to identify and remediate the organizational factors that are presently leading to the faulty delivery of a professional development framework (PDFM) tool in an educational organization in the Canadian Arctic. Implementation of change initiatives in organizations is a complex undertaking and can be further complicated by contextual factors such as culture. In this region, a large percentage of students are Inuit, and teachers and school leaders are both Inuit and non-Inuit. Inuit Qaujimajatuqangit (IQ), translated as Inuit traditional knowledge, is a foundation upon which education is delivered in the region. Therefore, this organizational change requires the integration of (IQ) principles and cross-cultural awareness to ensure that students’ cultural and identity needs are met. The change plan is framed by a social constructivist worldview and incorporates transformational leadership approaches that have been identified as the best-suited ways to lead this change process. To ensure that the implementation of the PDFM tool is done with fidelity, this OIP proposes a change plan framed by Cawsey et al.’s (2016) change path model in conjunction with the conceptual framework of Hall and Hord’s (2006) concerns-based adoption model. This OIP further proposes that change path planning is viewed through the lens of the three dimensions of culturally responsive pedagogy: institutional, personal, and instructional. These three dimensions relate directly to the IQ principles, and embracing them in leadership will help to ensure that IQ is an integral part of implementation planning. The solution for change, to leverage school literacy teams to work as leadership development teams, builds upon the structures and procedures that presently exist in schools. The vision is to create a community of practice protocol to develop and strengthen leadership capacity in schools. With this increased capacity, school leaders will be able to execute the PDFM tool with success, supporting ...